Endotoxin tolerance in monocytes can be mitigated by α2‐interferon. Issue 4 (23rd July 2015) - Shi, Lihua; Song, Li; Maurer, Kelly; Sharp, James; Zhang, Zhe; Sullivan, Kathleen E.
Abstract : IFN‐α can reverse tolerance by re‐establishing permissive chromatin marks, and tune its responses to pathogens. Abstract : Endotoxin tolerance is characterized by diminished expression of inflammatory cytokines after sequential exposure to Toll‐like receptor stimuli. Many mechanisms contribute to tolerance; however, chromatin remodeling appears to be the most significant regulator. The type II interferon, IFN‐γ, has been recognized as being able to reverse or abrogate the establishment of tolerance. Type I interferons have not been investigated previously, and they bind a distinct receptor. We found that α2‐interferon was able to abrogate or diminish tolerance by endotoxin, as defined by measuring mRNA levels at recognized tolerance targets. We also found that α2‐interferon treatment during tolerization was associated with increased H3K4me3 and H3K4me2 levels at promoters of tolerance targets in THP1 cells. These marks were normalized after exposure of the cells to α2‐interferon. Interferon regulatory factor 1 is a transcription factor activated and induced by types I and II interferons. We found recruitment of this transcription factor paralleled tolerance and inhibition of tolerance at target genes. Therefore, there are at least 2 distinct pathways by which endotoxin tolerance may be mitigated. A type I interferon, in spite of binding to a different receptor, was just as able to inhibit tolerance as the type II interferon and also appeared to act by modifying chromatin at tolerance target genes.